Service Quality in the P2P Economy: SERVQUAL Applied to Airbnb Listings in World Heritage Site - Portolan, Ana (Oeconomica Jadertina, 2026)
As a result of the rapid growth of peer-to-peer (P2P) as an innovative business model in the hospitality industry and the need for world heritage sites (WHS) protection from over-tourism development, investigating the service quality of P2P accommodation in WHS is of paramount importance. The main purpose of this paper was to identify which service dimensions in P2P accommodation in WHS have been evaluated by guests as of the highest quality. To achieve the main purpose of this paper, empirical research was conducted using a convenience sample of 352 tourists who had used P2P accommodation in the Dubrovnik WHS between April and October 2022 and between May and October 2023. Based on empirical research using the SERVQUAL model, tourists had the lowest expectations for hosts’ empathy and responsiveness, compared with tangible elements in accommodation units, which they expected the most. The results indicated that, in WHS, the most prominent dimension of P2P accommodation units, based on perceptions, is responsiveness. Additionally, tourists who stayed in P2P accommodations in the Dubrovnik WHS rated empathy and responsiveness as the two highest-rated quality dimensions. In addition to its theoretical contribution, the findings of this paper could serve as guidelines for categorizing P2P accommodation in WHSs and as indicators for hosts in WHSs of what needs to be upgraded and improved. The results could also help urban planners and P2P promoters in WHS assess the degree of reality or exaggeration in P2P. Given the limitations of this paper and considering the research area and sample, future research should examine more WHSs and conduct comparative analyses of P2P accommodation quality outside WHSs.